Koncepcja klastrów na obszarach wiejskich Pomorza Zachodniego jako szansy na podniesienie konkurencyjności MŚP agrobiznesu - Łącka, Irena (The Conception of Clusters on Rural Areas of West Pomerania as a Chance to Increase Competitiveness of SME's of Agribusiness, 2006)
The article discusses the author's conception of food cluster on Western Pomerania. The authoress regards clusters in rural areas as a chance to increase competitiveness of agribusiness of SME's and the region. She discusses a notion and essence of working of cluster as well as possibilities of its organizing in sector of food processing in West Pomeranian Region.The article shows rules of its organization as well as a way of funding of workings which support undertaking such as agreement between sector of the SME's, tradesmen, recipient, centres of R&D, universities, institutions supporting business, financial institutions and authorities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 47-53